INFLUÊNCIA DA ϵ-Caprolactona NA NANOENCAPSULAÇÃO DE ÓLEO ESSENCIAL DE MANJERICÃO Ocimum basilicum - OLIVEIRA, Vitoria Santos Teixeira; VENTURA, Arlene Sobrinho; ARRUDA, Gilberto José; Claudia Andrea Lima (ANAIS DO ENIC, 2025)
-